Determinants of migration in Brazil: regional polarization and poverty traps - BRAZ-GOLGHER, André; ROSA, Carlos Henrique; DE ARAÚJO-JUNIOR, Ari Francisco (Papeles de Población; Vol. 14 Núm. 56 (2008), 2008)
In the present study, we used the neoclassic human capital model as the theoretical foundation for the analyses of the determinants of migration in Brazil. In order to do so empirically, we applied a multiple regression macro model of migration based on the gravity model and on the Poisson distribution. In the empirical model, the number of migrants between Brazilian mesoregions was the response variable, and socioeconomic and criminal regional aspects, as well as geographical dummies were the explanatory ones. The influence of the distance in the migratory process was analyzed and also the power of regional polarization by urban centers. The determinants of migration when applied to migrants in different income strata showed the evidence of  poverty traps in the Northeast Region in Brazil, the poorest area of the country.